Seven-Year Trend Analysis Of Dyslipidemia Among Patients Reporting To Tertiary Care Hospital In Rawalpindi, Pakistan - Waheed, Alishba; Nafisa, Asma; Omer, Wafa; Amin, Huma; Tariq, Amina; Umar, Muhammad (Journal of Rawalpindi Medical College, 2025)
Objective: Dyslipidemia is a noticeable cause of morbidity and mortality. The purpose of the study was to analyse the cholesterol and triglyceride levels of patients presenting for lipid profile. Methods: A total of 9989 participants presenting to Benazir Bhutto Hospital, Rawalpindi, for the Lipid profile assessment were enrolled in this study. The participants were included irrespective of age and gender. Data was retrieved from HMIS for the last 7 years (2015-2022). Enzymatic colourimetric techniques were used to examine the serum levels of total cholesterol and triglycerides. Dyslipidemia was defined based on standard guidelines by the National Cholesterol Education Program Adult Treatment Panel III. Results: Out of the total of 9989 presented with signs and symptoms of dyslipidemia, 401(4%) were subjects under 19 years of age. Among the adult patients, 4283(44 .7%) were males and 5305 (55.3%) were females. Females have significantly high concentrations of cholesterol median (min-max), 203.25(48-1157) as compared to males, 196.95 (2-924). Mann Whitney, p value= 0.0001. Significant. difference was not observed for the concentrations of triglycerides in both genders (p=0.761) Substantial difference in concentrations of cholesterol and triglycerides was observed in different age groups Kruskal Wallise H 145.09 p –value 0.0001, Kruskal Wallise H 171 51 .09 p –value 0.0001 , respectively. Conclusion: Highest number of patient with dyslipidemia were observed in age group between 40-52 years. Mean cholesterol level in females were significantly higher as compared to males. Prevalence of isolated hypercholesterolemia and isolated hypertriglyceridemia in our study was 50.3% and 59.9% respectively.